Communicative Abilities of Pupils as Enhanced by Social Media - Abella, Loreliza (Journal of Interdisciplinary Perspectives, 2024)
This study aimed to determine the communicative abilities of pupils as enhanced by social media. The researcher applied the descriptive-correlational design and considered the 854 Grade 1 pupils in public and private schools as the respondents of the study. The researcher utilized a standardized questionnaire in communicative abilities of pupils as enhanced by social media. She employed the percent, weighted mean, multiple regression analysis, and Mann-Whitney U Test for treating the data. The study revealed that the communicative abilities of pupils in English was enhanced due the due to the following factors: (a) the parents educational level are college graduate, (b) the learners frequently visited social media sites; “YouTube”, “Facebook”, and TikTok”, (c) the learners frequently view television/ YouTube videos with parental guidance. Moreover, it was revealed that the parents’ and learners’ profile is significantly related to the level of ability in communicating in English. The study also found out that the parents’ and teachers’ perceptions on the learners’ level of ability in communicating in English is significantly different. The study came to the conclusion that pupils' proficiency in English was improved by parents' educational background, the language used at home, watching both educational and non-educational videos, and using social media under parental supervision.